(untitled) - Zauderer, Erich (Hoboken, N.J., 2006)
A revised and expanded edition of the applied partial differential equations work. This comprehensive, self-contained treatment discusses mathematical models that give rise to PDE's, classifies the equations and problems into different types, and examines exact and approximate methods for solution of these problems. Addresses problems that involve both linear and nonlinear equations of the three basic types, parabolic, hyperbolic, and elliptic. Coverage ranges from solution methods for first-order PDE's to perturbation and asymptotic methods for solving linear and nonlinear higher order equations. Includes a substantial number of new exercises and examples, many with answers. Chapter order is flexible enough to be used for full-year or one-semester courses.
Keywords: Differential equations, partial